The SAGE handbook of remote sensing - Foody, Giles M.; Warner, Timothy A.; Nellis, M. Duane (SAGE, 2008)
Developments in remote sensing technology have greatly extended the range of data available to those studying the Earth from a distance. A remote sensing analyst can now choose from a wide range of spatial, spectral, temporal and radiometric scales to address a particular question.